Situation Awareness Prompts: Bridging the Gap between Supervisory and Manual Air Traffic Control. Issue 29 (2022) - Kim, Munyung; Borst, Clark; Mulder, Max
Abstract: To meet increasing safety and performance demands in air traffic control (ATC), more advanced automated systems will be introduced to assist human air traffic controllers. Some even foresee complete automation, with the human as a supervisor only to step-in when automation fails. Literature and empirical evidence suggest that supervising highly-automated systems can cause severe vigilance and complacency problems, out-of-the-loop situation awareness and transient workload peaks. These impair the ability for humans to successfully take over control. In this study, situation awareness prompts were used as a way to keep controllers cognitively engaged during their supervision of a fully automated ATC system. Results from an exploratory human-in-the-loop experiment, in which eight participants were instructed to monitor a fully automated ATC system in a simplified ATC context, show a significant decrease in workload peaks following an automation failure after being exposed to high-level SA questions. Although the selected method did not necessarily yield improved safety and manual control efficiency, results suggest that using situation awareness feedback in line with controllers' attention could be an avenue worth exploring further as a training tool.